2013
DOI: 10.1371/journal.pone.0072444
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Outcomes, and Costs of Antenatal, Well-Baby, and Prevention of Mother-to-Child Transmission of HIV Services under Routine Care Conditions in Zambia

Abstract: BackgroundZambia adopted Option A for prevention of mother-to-child transmission of HIV (PMTCT) in 2010 and announced a move to Option B+ in 2013. We evaluated the uptake, outcomes, and costs of antenatal, well-baby, and PMTCT services under routine care conditions in Zambia after the adoption of Option A.MethodsWe enrolled 99 HIV-infected/HIV-exposed (index) mother/baby pairs with a first antenatal visit in April-September 2011 at four study sites and 99 HIV-uninfected/HIV-unexposed (comparison) mother/baby p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The study consisted of ART naïve pregnant women while the study had both naïve and ART-experienced participants and ARV-naive pregnant women are more likely to achieve viral loads <1000 copies/mL compared to those who are ARV-experienced. 6 The study results also indicated that majority of the women 89.7% (n=286) HIV pregnant women have suppressed with VL <1000 copies/mL compared to 10.3% (n=33) that were not suppressed (VL >1000 copies/mL). The high viral suppression rates were comparable to another study conducted in Uganda with 96% (67/70) pregnant and lactating women on option B+ suppressed at 6 months, 93.1% (174/187) at 12 months and 95.8% (479/500) at 24 months with suppression VL<1000 copies/mL 12 and also report a viral suppression rate (VL<1000 copies/mL) of 90% (n=448) among pregnant and breastfeeding women enrolled on option B+ in 13 large health facilities in Malawi.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The study consisted of ART naïve pregnant women while the study had both naïve and ART-experienced participants and ARV-naive pregnant women are more likely to achieve viral loads <1000 copies/mL compared to those who are ARV-experienced. 6 The study results also indicated that majority of the women 89.7% (n=286) HIV pregnant women have suppressed with VL <1000 copies/mL compared to 10.3% (n=33) that were not suppressed (VL >1000 copies/mL). The high viral suppression rates were comparable to another study conducted in Uganda with 96% (67/70) pregnant and lactating women on option B+ suppressed at 6 months, 93.1% (174/187) at 12 months and 95.8% (479/500) at 24 months with suppression VL<1000 copies/mL 12 and also report a viral suppression rate (VL<1000 copies/mL) of 90% (n=448) among pregnant and breastfeeding women enrolled on option B+ in 13 large health facilities in Malawi.…”
Section: Discussionmentioning
confidence: 71%
“…Detectable VL or none suppression is highest among women that enrol on option B+ with ≤ 4 months of ART. 6,7 The results of this study emphasized the need to intensify support for HIV pregnant women on option B+ during the early months of ART initiation. Most of the respondents in the study at the start of ART presented with high CD4 count with a median of 349.68 cells/µL and IQR (1-1012) and less advanced WHO Treatment stage with 96.9% (n=309) staged as WHO stage 1 and 3.1% (n=10) as stage 2, report that 70.5% of breastfeeding and pregnant women on option B+ in Northeast Ethiopia initiate ART with WHO clinical stage 1 and 6.6% with stage 2.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We first estimated that the cost of syphilis screening per patient was $3.10 (see Table 1 ), of which $1.53 was for materials (the test kit and other minor supplies), $1.03 was for health worker time ( Table 4 ), and $0.54 was for health worker training ( Table 4 ). For perspective, an HIV test is also completed during the first visit for antenatal care, and the materials for an HIV test costs less than $1 [16] , with a confirmatory test for those testing positive less than $2. A recent study from Southern Province of Zambia reported that the cost of antenatal and postnatal care for mother/baby pairs through six months post-partum was $31 for HIV-negative mothers and $69 for HIV-positive mothers (not including costs of antiretroviral therapy) [16] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, low uptake of antenatal care (ANC) services, stigma and lack of disclosure negatively impact PMTCT programs (4). In Zambia reports that HIV-infected women attending PMTC programs present to care late in pregnancy and many are lost to follow up by six months postpartum (5). Similarly, a systematic review conducted among 44 studies in Sub-Saharan Africa assessing barriers and facilitating factors of ART in PMTCT reveals that inadequate knowledge on HIV, ART and vertical transmission; lower maternal education level, stigma, poor staffclient interactions, service accessibility, and non-facility deliveries are among the barriers or factors Option B+ includes the period from pregnancy to lactation which therefore targets both pregnant and lactating women.…”
Section: Introductionmentioning
confidence: 99%